2009
DOI: 10.1590/s1676-06032009000100020
|View full text |Cite
|
Sign up to set email alerts
|

Anuros do cerrado da Estação Ecológica e da Floresta Estadual de Assis, sudeste do Brasil

Abstract: Abstract:The Brazilian cerrado is a hotspot of biodiversity, areas with many endemic species subjected to severe habitat loss. About 150 amphibian species are known to the Brazilian cerrado, and 28% of them are endemic. Studies focusing cerrado anuran communities are rare. Here we provide a commented list of anurans of two conservation unities of the municipality of Assis, southeastern Brazil: the Estação Ecológica de Assis and the Floresta Estadual de Assis. Twenty three anuran species were recorded, and thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
2
12
0
14
Order By: Relevance
“…Em geral, espécies de matas de encostas não apresentam grandes agregações para a reprodução, ao passo que espécies de áreas abertas se congregam em altas densidades durante a estação reprodutiva (Wells, 1977, Ribeiro-Júnior, 2009Loebmann e Haddad, 2010).…”
Section: Principais Sítios De Reprodução Dos Anfíbios Anuros Em Petrounclassified
“…Em geral, espécies de matas de encostas não apresentam grandes agregações para a reprodução, ao passo que espécies de áreas abertas se congregam em altas densidades durante a estação reprodutiva (Wells, 1977, Ribeiro-Júnior, 2009Loebmann e Haddad, 2010).…”
Section: Principais Sítios De Reprodução Dos Anfíbios Anuros Em Petrounclassified
“…Hypsiboas lundii is a species that occurs in gallery forests where males can be observed calling on the arboreal strata at the banks of permanent water bodies (Zina et al 2007, Oda et al 2009, Ribeiro-Júnior & Bertoluci 2009 (Toledo et al 2003), which may explain why these species were infrequent and only found when it rained enough for the formation of temporary ponds in open areas near the lake.…”
Section: Species Compositionmentioning
confidence: 99%
“…Segundo Haddad (1998), o Cerrado paulista apresenta uma anurofauna naturalmente mais empobrecida em relação às áreas de Mata Atlântica, pois os ambientes abertos desse ecossistema permitem poucas especializações reprodutivas aos anuros, restringindo o número de grupos filogenéticos que podem ocupar estas áreas. Os levantamentos de anuros no Cerrado paulista foram realizados em áreas de transição com Floresta Estacional Semidecidual (e.g., Jim 1980, 2003, Bernarde & Kokubum 1999, Vasconcelos & Rossa-Feres 2005, Araujo et al 2009b, cerradão (e.g., Melo et al 2007, Ribeiro Junior & Bertoluci 2009) e cerrado aberto (Brasileiro et al 2005). No presente trabalho, apresentamos uma lista de espécies de anuros em uma lagoa em área de cerrado aberto no município de Borebi (SP), caracterizamos a distribuição das espécies na lagoa estudada e descrevemos a variação sazonal das espécies registradas.…”
Section: Introductionunclassified